Studi Kelayakan Bisnis Pembangunan Hotel ABCD dari Aspek Pasar dan Pemasaran - Hambali, Hasan; Prihanto, Agus (Prasetiya Mulya Publishing, 2022)
The city of Bekasi is a city industry, trade and services making the city of Bekasi suitable to be used as a good investment place. The level of tourist visits that always increases every year makes the level of hotel visits always increases every year. Hotel development requires a large amount of financing, making business studies necessary. This research methodology uses a qualitative descriptive method. The results of the analysis show that the market and marketing aspects include market segmentation, guests from Indonesia and abroad, etc. SWOT includes Strengths of the hotel to be built has many advantages, Weaknesses in the form of traffic jams and Bekasi is not a tourist city, Opportunities have high opportunities by looking at high demand for rooms, Threats of having several competitors who already have names. The conclusion from the above analysis can be said that the ABCD hotel from the market and marketing aspects is feasible to build.